Minimal invasive extracorporeal circulation preserves coagulation integrity. (April 2022) - Argiriadou, Helena; Antonitsis, Polychronis; Gkiouliava, Anna; Papapostolou, Evangelia; Deliopoulos, Apostolos; Anastasiadis, Kyriakos
Introduction: Coagulopathy after cardiac surgery is a serious multifactorial complication that results in postoperative bleeding requiring transfusion of red blood cells and procoagulant products. Use of cardiopulmonary bypass represents the major contributing factor affecting coagulation. We sought to prospectively investigate the effect of contemporary minimal invasive extracorporeal circulation (MiECC) on coagulation parameters using point-of-care (POC) rotational thromboelastometry and the relation to postoperative bleeding. Methods: Patients undergoing elective cardiac surgery on MiECC were prospectively recruited. Anticoagulation strategy was based on individualized heparin management and heparin level-guided protamine titration. Rotational thromboelastometry testing was performed before induction of anesthesia and after aortic cross-clamp release. A strict POC-guided transfusion protocol was implemented. The primary endpoint was the assessment of viscoelastic properties of the coagulating blood at the end of surgery compared to preoperative values and the relation to postoperative bleeding and 24-hour transfusion requirements. Results: Fifty patients were included in the study with a significant proportion having complex surgery. Thirteen patients (26%) required blood transfusion (mean rate: 0.5 ± 1 units per patient), 5/50 (10%) received coagulation factors while no patient received fresh frozen plasma, platelets or fibrinogen. Thromboelastometry analysis showed that the major derangement was CT EXTEM > 100 seconds in 28/50 (56%) and A10 EXTEM < 40 mm in one (2%) patient without clinical significance. Platelet function was preserved throughout surgery. A10-FIBTEM was found predictive of postoperative bleeding at 12 hours. Conclusions: MiECC preserves clot quality throughout surgery acting in both key determinants of clot strength; fibrinogen and platelets. This is clinically translated into minimal postoperative bleeding and restricted use of blood products and coagulation factors.